Craniocerebral Gunshot Injuries; A Review of the Current Literature - Hernando Raphael Alvis-Mirand; Andres M. Rubiano; Amit Agrawal; Alejandro Rojas; Luis Rafael Moscote-Salazar; Guru Dutta Satyarthee; Willem Guillermo Calderon-Miranda; Nidia Escobar Hernandez; Nasly Zabaleta-Churio (Bulletin of Emergency and Trauma, 2016)
Craniocerebral gunshot injuries (CGI) are increasingly encountered by neurosurgeons in civilian and urban settings. Unfortunately, more prevalent condition in developing countries, with major armed conflicts which is still persisting, since the main trigger is violence at the national or state level. Management goals of CGI should focus on aggressive resuscitation and correction of coagulopathy; those with stable vital signs should undergo CT scan head at the earliest possible opportunity. Neuroimaging is vital for planning of surgical management, especially to determine the type of surgery, routes of the approach to the surgical target area and extraction of the impacted foreign bodies, however, surgical management is not always indicated. Although subset of such cases may be managed even with non-surgical management. The treatment comprises of immediate life salvaging resuscitative measures including control of the persistent bleeding, care of associated injury, management of raised intracranial pressure, prevention of cerebrospinal fistula formation by primary watertight dural repair and prevention of infection, through extensive debridement of contaminated, macerated or ischemic tissues; preservation of nervous tissue and restoration of anatomic structures through the hermetic sealing of dural and scalp defect. Recently, only few studies of craniocerebral penetrating injuries are published that too involving smaller patients sample sizes; although classic studies in the military and civil situation noticed associated relatively very high mortality and morbidity and psychological as well as economic impact on the affected individual, the family and the health system in providing ongoing care to the sufferers and society at large. Currently various measures are advocated with aim to reduce the incidence of CGI especially in civilian populations. It is highly necessary and immensely urgent to promote research in a neurocritical care of CGI to provide positive impact on improvement of the quality of life and further providing better care and reduction of overall health care cost.